Transcriptome analysis of malate-induced Schizochytrium sp. FJU-512 reveals a novel pathway for biosynthesis of docosahexaenoic acid with enhanced expression of genes responsible for acetyl-CoA and NADPH accumulation - Zhang, Mingliang; Gao, YangLe; Yu, Cui; Wang, Jun; Weng, Kexin; Li, Qin; He, Yongjin; Guo, Zheng; Zhang, Huaidong; Huang, Jianzhong; Li, Li (Frontiers in Microbiology, 2022)
Schizochytrium is one of the few oleaginous microalgae that produce docosahexaenoic acid (DHA)-rich lipids. In this study, global changes in gene expression levels of Schizochytrium sp. FJU-512 cultured with malate in a 15 L-bioreactor was analyzed using comparative transcriptomics. The changes were found mainly in the genes involved in oxidative phosphorylation, β-oxidation, and pentose phosphate pathways. Consequently, the global changes in genes associated with the pathways could lead to an increase in the influx throughputs of pyruvate, branched-chain amino acids, fatty acids, and vitamin B6. Our transcriptome analysis indicated pyruvate dehydrogenase E2 component and acetolactate synthase I/II/III large subunit as major contributors to acetyl-CoA biosynthesis, whereas glucose-6-phosphate dehydrogenase was indicated as the major contributor to the biosynthesis of NADPH. An increase in DHA titer of up to 22% was achieved with the addition of malate to the fed-batch culture of Schizochytrium sp. FJU-512. This study provides an alternate method to enhance DHA production in Schizochytrium sp. FJU-512 through malate induced upregulation of genes responsible for acetyl-CoA and NADPH biosynthesis.